Comparison of research experience and support needs of rural versus regional allied health professionals. (18th September 2015) - Pain, Tilley; Plummer, David; Pighills, Alison; Harvey, Desley
Abstract Objective We compared the research experience or support needs of allied health professionals in rural versus regional cities to identify if they were the same or different. Design Descriptive study using a cross sectional survey. Setting This study was carried within Queensland Health's northern six health services. Participants Queensland health staff classified as Health Practitioners. Interventions This survey was conducted as part of a research capacity building initiative within Queensland Health to increase AHPs' participation in research in regional cities and rural areas of Queensland. Main outcome measures Questions in the survey identified demographics, research experience, need for research support, research knowledge and beliefs about research. Data were compared using Chi‐square and t‐tests. Results The total response rate was 54.5% with 18% of the HPs located in rural communities of less than 5000 people and the rest from the three major cities in northern Queensland. Rural HPs have less research experience in most research activities than regional city HPs and need more research support. Rural HPs have more qualitative research experience than regional city HPs and research is perceived positively by both. Barriers to conducting research were similar across both groups and included insufficient time, lack of staff and no statistical support. Conclusion Rural HPs are younger and have less research experience than their counterparts working in regional cities. Therefore, building rural HP research capacity initiatives may require more access to facilitators such as the Research Fellows.